Symmetry in the Multidimensional Dynamical Analysis of Iterative Methods with Memory - Cordero, Alicia; Garrido, Neus; Torregrosa, Juan Ramón; Triguero-Navarro, Paula (Symmetry-Basel, 2022)
In this paper, new tools for the dynamical analysis of iterative schemes with memory for solving nonlinear systems of equations are proposed. These tools are in concordance with those of the scalar case and provide interesting results about the symmetry and wideness of the basins of attraction on different iterative procedures with memory existing in the literature.
Keywords: dynamical analysis; iterative schemes with memory; nonlinear systems; fixed and critical points; stability; JCR; Scopus